Virtual otolaryngology interest group meetings and didactic sessions in the COVID-19 pandemic. Issue 5 (15th September 2022) - Daines, Benjamin S.; Varman, Rahul; Cordero, Joehassin
Abstract: The COVID-19 pandemic has placed tremendous strain on medical education and prevented multiple in-person activities like specialty interest group meetings. Specialty interest groups are important resources for students interested in competitive fields like otolaryngology where they may find mentoring, research opportunities, and teaching sessions. To allow continued meetings despite COVID-19, the Texas Tech University Health Sciences Center otolaryngology interest group transitioned to virtual meetings and added student-led didactic sessions. Most students who participated found the virtual didactic sessions helpful and appreciated the opportunity to practice presenting cases. Students were able to network with residents and faculty members, resulting in 60% of participants finding involvement in research projects. Virtual meetings allowed the participation of students from multiple institutions. Participants agreed that the networking, teaching, and research opportunities presented by the virtual sessions made them better applicants for otolaryngology residency. This study provides a framework for transitioning specialty interest group meetings to a virtual platform while adding student-led didactic sessions.